RCS Analysis of Target and Clutter in FMCW Radar - Ho, Jongun; Kim, Daehyun; Choi, Wonjong; Kim, Younglok (International Journal of Engineering and Technology, 2026)
The radar cross section (RCS) of a target is used to identify it and to glean its characteristics, by measuring the size of reflected radar signal. In this study, we used a 77 GHz triangular frequency modulated continuous wave (FMCW) array radar to detect pedestrians, automobiles, and clutter. It is possible to classify target and clutter by analyzing the characteristic of the measured RCS. In this study, suitable target RCS characteristics (mean, variance and probability distribution) were analyzed based on measured data.